Kontrol Diri dan Harapan Keberhasilan Studi Pada Siswa Sma - Amatullah, Azzahra Isdihar; Musthofa, Wakhid (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2023)
Hope of Academic success is an important theoretical framework to guide students' research and practice in the future. One of the factors that influence hopes is self-control. This study aims to determine the relationship between self-control with high school students' Hope of Academic success. The sample amounted to 106 which is located in SMA Al Islam 1 Surakarta. The results of the analysis of research data showed a correlation coefficient of 0.672 with a significance value of 0.000 (p < 0.05). The results of this correlation can be interpreted that the alternative hypothesis (Ha) that there is a positive relationship between self-control and the expectation of successful high school students' studies can be accepted. The implication of this research is that high school students can apply good self control efforts in order to have hopes of academic success so that the chances of student success in the selection of state universities are high.